HUBUNGAN POWER OTOT TUNGKAI DAN KELENTUKAN PUNGGUNG DENGAN KETEPATAN JUMP SMASH PADA ATLET BULU TANGKIS PB REALITA KECAMATAN MARPOYAN DAMAI - Bedri Romi; Slamet Slamet; Aref Vai (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The research problem of this study to know the Correlation of Limb Muscle Power and Back Flexibility with Jump Smash Accuracy in PB Reality Badminton Athlete. This research has been conducted on 2 July 2020 at GOR Bulu Tangkis PB Realita Kecamatan Marpoyan Damai Pekanbaru. The design of this research was using Saturation Sampling Technique. Furthermore, the sample and population research consisted of 15 people in PB Reality Badminton Athlete. Analysis of the data in this study using statistical techniques. The result of variable X1 leg muscle power to variable Y, the jump smash accuracy, rcount 0.834 > rtabel 0.514 which means that there is a significant data. Next, for the result of variable X2 Back Flexibility to variable Y, the jump smash accuracy rcount 0.639 > rtabel 0.514 which means that there is significant data, it is the same with variable X1. The outcome of variable XI leg muscle power and X2 Back Flexibility toward Jump Smash Accuracy as variable Y is rcount 0.851 > rtabel 0.514. The Conclusion of this research, there is significant data between Leg Muscles Explosive Power and Back Flexibility to Jump Smash Accuracy in PB Reality Badminton Athlete.Key Words: Leg Muscle Power, Back Flexibility, and Precise Jump Smash